Preparation and Quality Evaluation of Soy Corn Yoghurt - Shrestha, Suman Lal; Yadav, Ram Shovit (Himalayan Journal of Science and Technology, 2018)
Soy corn yoghurt is a vegan friendly product prepared by using soymilk as the major ingredient. The aim of this study was to assess the effect of corn milk addition (0, 10, 20, 25 & 30%) on the quality of soy yoghurt. The samples were subjected to sensory evaluation for consumer acceptability and data were subjected to statistical analysis. From sensory evaluation and statistical analysis 10% corn milk inclusion was selected as the best product (p